2013
DOI: 10.1093/icvts/ivt022
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of original EuroSCORE, EuroSCORE II and STS risk models in a Turkish cardiac surgical cohort†

Abstract: EuroSCORE II significantly underestimated mortality risk for Turkish cardiac patients, whereas additive and logistic EuroSCORE and STS risk calculators were well calibrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
1
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 18 publications
4
47
1
5
Order By: Relevance
“…(23) In another study comparing the EuroSCORE II in a Turkish cohort of 428 patients, the model was shown to underestimate mortality risk for the entire cohort. (24) Our study cohort, though small, showed a similar pattern with the predicted mortality being underestimated in the entire cohort but overestimated in the lower risk AVR and MV repair groups. In addition, the EuroSCORE II had a better discriminatory ability for early mortality in the AVR group than the other sub-groups in our study.…”
Section: Infective Endocarditissupporting
confidence: 70%
“…(23) In another study comparing the EuroSCORE II in a Turkish cohort of 428 patients, the model was shown to underestimate mortality risk for the entire cohort. (24) Our study cohort, though small, showed a similar pattern with the predicted mortality being underestimated in the entire cohort but overestimated in the lower risk AVR and MV repair groups. In addition, the EuroSCORE II had a better discriminatory ability for early mortality in the AVR group than the other sub-groups in our study.…”
Section: Infective Endocarditissupporting
confidence: 70%
“…The differences between AUC of addES and the AUC of ESII in both examined groups were statistically significant (Table 4). In contrast to this data, the addES remained good in three studies performed by Kunt et al [9], Toumpoulis et al [17], and in a CABG cohort from Akgül et al [11]: AUC: 0.70 and 0.72, 0.992, respectively.…”
Section: Discriminatory Powercontrasting
confidence: 62%
“…The mortality rate in our study was at the level of 5.21% and it did not differ with the background of other similar studies, in which this value ranged from 2.2% to 5.66% [8][9][10][11][12][13]. For our CABG patients, this value was 5.33%.…”
Section: Discriminatory Powersupporting
confidence: 57%
“…Later on, another scoring system by The Society of Thoracic Surgeons (STS) was described, and published [12]. STS scoring system which is more detailed relative to the EuroSCORE system has demonstrated its superiority over EuroSCORE in many cardiac surgery groups [13-15]. However clinical application of STS scoring system is very difficult.…”
Section: Discussionmentioning
confidence: 99%